2022
DOI: 10.3390/foods11162467
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Food Literacy, Health Promotion Literacy and Healthy Eating Habits among Young Adults in South Korea

Abstract: The obesity problem has reached a critical level and is threatening not only personal health but also public health systems around the world. Obesity in young adults is especially rapidly growing and many studies have confirmed that the best prevention is developing healthy eating habits with the improvement of food and health promotion literacy competencies. In this context, this study diagnoses the present levels of food literacy and health promotion literacy among young adults and explores the relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 95 publications
(142 reference statements)
3
19
0
Order By: Relevance
“…This conclusion could be explained by the fact that people with low food literacy are more likely to engage in high-risk eating behaviors that lead to weight gain. Risky eating habits contributing to weight gain include a diet high in fast food, skipping meals, and consuming a disproportionate number of processed foods (47). Compared to those with chronic disease(s), healthy participants had a 60.0% higher probability of expressing poor food literacy in the current study; this link may be due to parents dealing with chronic disorders needing to consult doctors and dietitians more often.…”
Section: The Correlates Of Parental Food Literacymentioning
confidence: 70%
“…This conclusion could be explained by the fact that people with low food literacy are more likely to engage in high-risk eating behaviors that lead to weight gain. Risky eating habits contributing to weight gain include a diet high in fast food, skipping meals, and consuming a disproportionate number of processed foods (47). Compared to those with chronic disease(s), healthy participants had a 60.0% higher probability of expressing poor food literacy in the current study; this link may be due to parents dealing with chronic disorders needing to consult doctors and dietitians more often.…”
Section: The Correlates Of Parental Food Literacymentioning
confidence: 70%
“…Similarly, a study in the United States found that high school graduates ate less healthy than adults with some college education or more [ 58 ]. In South Korea, higher education was positively associated with adults’ healthy eating habits [ 59 ]. Furthermore, higher income participants' consumption of healthy foods may explain income differences in which lower income participants are unable to cover the cost of a healthy food.…”
Section: Discussionmentioning
confidence: 99%
“…Although not statistically significant, those with higher health literacy scores tended to have a lower chance of worsening dietary quality. Health and food literacy are associated with healthy eating habits [ 33 , 34 , 35 , 36 ]. A significant relationship was found between healthy eating literacy scores and a well-balanced diet among Japanese adults.…”
Section: Discussionmentioning
confidence: 99%